2016
DOI: 10.1093/abbs/gmv118
|View full text |Cite
|
Sign up to set email alerts
|

Targeting KRAS-mutant non-small cell lung cancer: challenges and opportunities

Abstract: Oncogenic mutations in Kirsten rat sarcoma viral oncogene homolog (KRAS) occur in 15%-30% of non-small cell lung cancer (NSCLC). However, despite decades of intensive research, there is still no direct KRAS inhibitor with clinically proven efficacy. Considering its association with poor treatment response and prognosis of lung cancer, developing an effective inhibitory approach is urgently needed. Here, we review different strategies currently being explored to target KRAS-mutant NSCLC, discuss opportunities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…In clinical trials FTIs did not show activity in NSCLC, and they have never been tested in a defined KRAS mutant population [ 10 , 50 ]. A possible explanation for the FTIs failure may be the presence of an alternative modification, the geranylgeranylation, that is another process to localize protein to the membrane (Figure 2 ) [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…In clinical trials FTIs did not show activity in NSCLC, and they have never been tested in a defined KRAS mutant population [ 10 , 50 ]. A possible explanation for the FTIs failure may be the presence of an alternative modification, the geranylgeranylation, that is another process to localize protein to the membrane (Figure 2 ) [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mutant KRAS activates over a dozen downstream targets to assert its protumorigenic effects and the RAF/MEK/ERK pathway is among one of the most wellcharacterized (15). In fact, many approaches to targeting mutant KRAS cancers involve the utilization of MEK/ERK inhibitors (27)(28)(29)(42)(43)(44). Our work revealed that KRAS regulates SREBP1 expression via MEK/ERK activation.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies showed that MEK/ERK regulate translation (26). Therefore, we treated 293T cells transfected with SREBP1 and KRAS with the MEK inhibitor AZD6244 (27)(28)(29). MEK inhibition greatly blunted the effect of KRAS on SREBP1 protein expression compared to vehicle control (Figure 3a).…”
Section: Oncogenic Kras Regulates Srebp1 Protein Expression Via Mek1/mentioning
confidence: 89%
“…v-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog (KRAS) is a very important oncogene for the initiation of cancer [1]. It is usually found to be mutated in different types of cancer, particularly in colorectal cancers (CRCs), pancreatic cancer (PC), and lung cancer [4][5][6]. Concerning KRAS, different chemicals such as polychlorinated biphenyls (PCBs), certain antidiabetic drugs, and pesticides may be leading causes of KRAS mutations, and such mutations increase the expression of K-Ras protein in different tissues, leading to high cellular proliferation and finally carcinogenesis [7][8][9].…”
mentioning
confidence: 99%